2022
DOI: 10.3390/ma15051962
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of a New Calcium Silicate-Based Root Canal Sealer Mediated via the Modulation of Macrophage Polarization in a Rat Model

Abstract: (1) Background: The EndoSequence BC Sealer HiFlow (Brasseler, Savannah, GA, USA) has recently been introduced in clinical applications. Thus, the aims of the present study are to determine its biocompatibility in vivo and to examine its ability to drive macrophage polarization in vitro and in vivo. (2) Methods: HiFlow was implanted into rat connective tissue for 7, 30 and 150 days. The microstructures and elemental compositions were determined by scanning electron microscopy-energy-dispersive X-ray spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
3
12
0
Order By: Relevance
“…Two studies using an elemental mapping analysis showed that EBC and TCLC induce apatite formation in rat subcutaneous tissue, but MTAF did not induce apatite formation [5,18]. In addition, one study detected apatite formation on EBC after in vivo implantation using a scanning electron microscope-energy dispersive X-ray spectrometry [19]. Our current ndings, based on Raman spectroscopy, are consistent with these previous ndings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Two studies using an elemental mapping analysis showed that EBC and TCLC induce apatite formation in rat subcutaneous tissue, but MTAF did not induce apatite formation [5,18]. In addition, one study detected apatite formation on EBC after in vivo implantation using a scanning electron microscope-energy dispersive X-ray spectrometry [19]. Our current ndings, based on Raman spectroscopy, are consistent with these previous ndings.…”
Section: Discussionsupporting
confidence: 88%
“…Numerous studies focused on the apatite-forming ability of different types of second-generation HCSCs in vitro by immersing the materials in arti cial body uids, such as Kokubo's simulated body uid [12], Hank's balanced salt solution [13], and phosphate-buffered saline [14][15][16]. However, only a few studies investigated the apatite-forming abilities of second-generation HCSCs in vivo [17][18][19][20]. Furthermore, recent studies demonstrated that apatite is more di cult to form on HCSCs in vivo compared with apatite formation in arti cial body uids in vitro [17,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the inflammatory reaction was reduced in all groups 28 days after implantation, and no additional inflammatory reaction was observed compared to the control. The reduction in inflammatory cells was a result of a similar phenomenon reported in a rat subcutaneous model that evaluated different types of RCO sealers than those used in the present study [ 29 ]. These results suggest that the RCO sealers used in the present study have high biocompatibility.…”
Section: Discussionsupporting
confidence: 77%
“…Even at higher temperatures, Endosequence BC Sealer HiFlow showed excellent flow, reduced viscosity, and the functional groups of this sealer were not altered [ 52 ]. Based on the findings of the previous investigation, Endosequence BC Sealer HiFlow showed good biological properties in terms of cell viability [ 35 ], cell migration, adhesion, promotion of mineralization, and ALP activity as well as upregulation of RUNX2 expression by h PDLSCs [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%